2019
DOI: 10.18203/2394-6040.ijcmph20191552
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude, and practice regarding hepatitis B among medical students in a private medical college in Kochi

Abstract: Background: Hepatitis B virus is transmitted by body fluids, such as blood and serum. Sexual transmission, vertical transmission, and unsafe injections, including intravenous drug use, are the most common routes of infection for Hepatitis B infection. Medical students have a very important role in preventing the disease by improving the disease knowledge among themselves and the patients they will eventually treat.Methods: A cross sectional study was conducted to assess the KAP among medical students of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 3 publications
5
6
2
Order By: Relevance
“…In the current study, majority (95.6%) of the respondents had good knowledge of hepatitis B vaccination. Similar, good knowledge were demonstrated by 77.07% and 79.1% in the studies by Vasantha et al 8 and Jacob et al 9 in India respectively. But in Senegal, majority of 73% showed poor knowledge in the study by Fortes et al 10 Among the respondents in the current study, 83.3% knew that hepatitis B is not spread by handshaking.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In the current study, majority (95.6%) of the respondents had good knowledge of hepatitis B vaccination. Similar, good knowledge were demonstrated by 77.07% and 79.1% in the studies by Vasantha et al 8 and Jacob et al 9 in India respectively. But in Senegal, majority of 73% showed poor knowledge in the study by Fortes et al 10 Among the respondents in the current study, 83.3% knew that hepatitis B is not spread by handshaking.…”
Section: Discussionsupporting
confidence: 81%
“…Poor practice was common among medical students in many studies as well. It was 55.2% and 66.6% in the Indian studies by Jacob et al 9 and Vasantha et al 8 Only 37.7% had tested for Hepatitis B in the current study, whereas, more than half (56.5%) and 55.6% had screened for HBV infection in the studies by Alhowaish et al 11 and Fortes et al 10 respectively. It was even better (79.5%) in the study by Vasantha et al 8 Many studies have demonstrated a low rate of complete vaccination among medical students.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations